2022
DOI: 10.1155/2022/8866660
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg2 Attenuated Trastuzumab-Induced Cardiotoxicity in Rats

Abstract: Aim. Trastuzumab (TZM) is a monoclonal antibody drug for HER2-positive breast cancer by targeting epidermal growth factor 2, but it has significant cardiotoxicity. Ginsenoside Rg2 has shown a variety of biological activities. This study was aimed at investigating whether Rg2 attenuates TZM-induced cardiotoxicity. Methods. A model of TZM-induced cardiotoxicity was established in Wistar rats, and the rats were pretreated with Rg2. After echocardiography analysis, the rats were killed and the hearts were dissecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Ginsenoside Rd was also reported to attenuate the mitochondria-dependent apoptotic pathway via Akt/GSK-3β signaling in myocardial ischemia/reperfusion injury (Wang et al 2013). Ginsenoside Rg2 (1) was previously reported to be capable of relieving cardiotoxicity induced by trastuzumab (Liu et al 2022), but no report on DOX. In our study, the anti-apoptotic function of ginsenoside Rg2 in DOXtreated cells was confirmed using TUNEL staining, of which the effect was dose-dependent.…”
Section: Upregulation Of Pi3k/akt Pathwaymentioning
confidence: 99%
“…Ginsenoside Rd was also reported to attenuate the mitochondria-dependent apoptotic pathway via Akt/GSK-3β signaling in myocardial ischemia/reperfusion injury (Wang et al 2013). Ginsenoside Rg2 (1) was previously reported to be capable of relieving cardiotoxicity induced by trastuzumab (Liu et al 2022), but no report on DOX. In our study, the anti-apoptotic function of ginsenoside Rg2 in DOXtreated cells was confirmed using TUNEL staining, of which the effect was dose-dependent.…”
Section: Upregulation Of Pi3k/akt Pathwaymentioning
confidence: 99%
“…GS also plays a significant role in immunotherapy and targeted therapy (Jiang et al, 2017;Liu J et al, 2022). Jiang et al observed that GRg3 enhances the anti-proliferative activity of erlotinib in pancreatic cancer cell lines by downregulating the EGFR/ PI3K/Akt signaling pathway (Jiang et al, 2017).…”
Section: Combined Use and Reversal Of Drug Resistancementioning
confidence: 99%
“…C-K blocked the interaction between membrane-linked protein A2 and the NF-кB p50 subunit and its nuclear co-localization, inhibited NF-кB activation, upregulated caspase-9 and caspase-3 expressions, and promoted apoptosis ( Wang X et al, 2019 ). Liu et al observed that C-K upregulates p21, a downstream target of RUNX3, arrests the cell cycle in the G0/G1 phase, and induces apoptosis ( Liu G et al, 2022 ). Reportedly, C-K induced apoptosis by inhibiting caspase and p53-dependent LGR5 expression in HCT116 colorectal cells ( Pak et al, 2020 ) and blocking HT-29 colorectal cells from entering the G1 phase, and C-K showed significant anti-inflammatory effects even at low concentrations ( Yao et al, 2018 ).…”
Section: Anti-tumor Mechanism Of Action Of the Active Ingredients Of ...mentioning
confidence: 99%
“…Rg2 induces autophagy in human cardiomyocytes (HCMs) by upregulating the expression levels of (p)-Akt, p-mTOR, beclin 1, light chain 3 (LC3) and autophagy protein 5 (ATG5), thereby treating TZM-induced cardiotoxicity ( Liu et al, 2021 ). Liu et al (2022) suggested that Rg2 could inhibit TZM-induced cardiac cytotoxicity. The mechanism might be related to the downregulation of proapoptotic proteins caspase-3, caspase-9, and BAX expression, which inhibited TZM-induced apoptosis in cardiac myocytes.…”
Section: Effects Of Ginsenosides On Cardiotoxicitymentioning
confidence: 99%